2007
DOI: 10.1002/cpp.519
|View full text |Cite
|
Sign up to set email alerts
|

Specific relationships between core beliefs and personality disorder symptoms in a non‐clinical sample

Abstract: The current study examined the relationship of clinically relevant core beliefs measured by the Young Schema Questionnaire-Short Form (YSQ-SF) to personality disorder (PD) symptoms in a large nonclinical sample (N = 804). Results indicated that the 15 YSQ-SF scales added sizeable explained variance (4% to 13%) to self-reported symptoms of 12 PDs, above variance explained by gender and symptoms of other PDs. In addition, several specific core beliefs related uniquely to individual PDs after controlling for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
54
5
5

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(71 citation statements)
references
References 27 publications
(24 reference statements)
7
54
5
5
Order By: Relevance
“…in this regard in different fields such as antisocial personality, avoidant personality, depressed personality, paranoid personality, dependent personality, borderline personality, and obsessive compulsive personality disorders which reveal a high correlation between early maladaptive schemas and these disorders (Ball & Cecero, 2001;Carr & Francis, 2010;Jovev & Jackson, 2004;Nordahl et al, 2005;Petrocelli, Glaser, Calhoun, & Campbell, 2001;Reeves & Taylor, 2007;Sines, Waller, Meyer, & Wigley, 2008;Specht, Chapman, & Cellucci, 2009). The findings of some researches on eating disorder also represented that the Emotional Deprivation, Social Isolation/Alienation, Defectiveness/Shame, Failure, Dependence/Incompetence, and Subjugation schemas are remarkably high in those patients (Anderson, Rieger, & Caterson, 2006;Leung, Waller, & Thomas, 1999;Moloodi, Dezhkam, Mootabi, & Omidvar, 2010;Riso, du Toit, Stein, & Young, 2007;Van Vlierberghe & Braet, 2007;Voderholzer et al, 2014;Waller, Meyer, & Ohanian, 2001), on the other hand active schemas in people suffering from drug abuse disorder are reported to be Subjugation, Vulnerability to Harm or Illness, and Emotional Inhibition (Ball & Cecero, 2001;Brotchie, Meyer, Copello, Kidney, & Waller, 2004).…”
mentioning
confidence: 99%
“…in this regard in different fields such as antisocial personality, avoidant personality, depressed personality, paranoid personality, dependent personality, borderline personality, and obsessive compulsive personality disorders which reveal a high correlation between early maladaptive schemas and these disorders (Ball & Cecero, 2001;Carr & Francis, 2010;Jovev & Jackson, 2004;Nordahl et al, 2005;Petrocelli, Glaser, Calhoun, & Campbell, 2001;Reeves & Taylor, 2007;Sines, Waller, Meyer, & Wigley, 2008;Specht, Chapman, & Cellucci, 2009). The findings of some researches on eating disorder also represented that the Emotional Deprivation, Social Isolation/Alienation, Defectiveness/Shame, Failure, Dependence/Incompetence, and Subjugation schemas are remarkably high in those patients (Anderson, Rieger, & Caterson, 2006;Leung, Waller, & Thomas, 1999;Moloodi, Dezhkam, Mootabi, & Omidvar, 2010;Riso, du Toit, Stein, & Young, 2007;Van Vlierberghe & Braet, 2007;Voderholzer et al, 2014;Waller, Meyer, & Ohanian, 2001), on the other hand active schemas in people suffering from drug abuse disorder are reported to be Subjugation, Vulnerability to Harm or Illness, and Emotional Inhibition (Ball & Cecero, 2001;Brotchie, Meyer, Copello, Kidney, & Waller, 2004).…”
mentioning
confidence: 99%
“…Because of this variability, these people can activate different EMSs at any given moment (Arntz & Genderen, 2009). Borderline PD often appears to be associated with schemas of the disconnection and rejection domain (Arntz & Genderen, 2009;Ball & Cecero, 2001;Jovev & Jackson, 2004;Reeves & Taylor, 2007). Dependent PD and related traits have mainly been associated with the domain of impaired autonomy and performance (e.g., the dependence schema; Schmidt, 1994) and with the disconnection and rejection domain (e.g., the abandonment schema; Carr & Francis, 2010;Gude, Hoffart, Hedley, & Rø, 2004;Nordahl, Holthe, & Haugum, 2005;Petrocelli, Glaser, Calhoun, & Campbell, 2001;Reeves & Taylor, 2007).…”
mentioning
confidence: 99%
“…Borderline PD often appears to be associated with schemas of the disconnection and rejection domain (Arntz & Genderen, 2009;Ball & Cecero, 2001;Jovev & Jackson, 2004;Reeves & Taylor, 2007). Dependent PD and related traits have mainly been associated with the domain of impaired autonomy and performance (e.g., the dependence schema; Schmidt, 1994) and with the disconnection and rejection domain (e.g., the abandonment schema; Carr & Francis, 2010;Gude, Hoffart, Hedley, & Rø, 2004;Nordahl, Holthe, & Haugum, 2005;Petrocelli, Glaser, Calhoun, & Campbell, 2001;Reeves & Taylor, 2007). Histrionic PD has been associated with the schema of subjugation within the other-directedness domain (Carr & Francis, 2010) and has been associated negatively with schemas such as mistrust and social isolation of the disconnection and rejection domain (Carr & Francis, 2010;Reeves & Taylor, 2007).…”
mentioning
confidence: 99%
“…found that vulnerability to harm, emotional inhibition, and insuicient self-control were associated with narcissistic personality disorder [39], in their nonclinical sample, Reeves and Taylor found that men endorsed more symptoms of ASPD and higher levels of the core beliefs of emotional deprivation, social isolation, defectiveness/shame, and emotional inhibition [40].…”
Section: Cognitive Behavioral Theory Of Antisocial Personality Disordermentioning
confidence: 92%